Astrocyte Ca2+ in the dorsal striatum suppresses neuronal activity to oppose cue-induced reinstatement of cocaine seeking - Tavakoli, Navid S.; Malone, Samantha G.; Anderson, Tanner L.; Neeley, Ryson E.; Asadipooya, Artin; Bardo, Michael T.; Ortinski, Pavel I. (Frontiers in Cellular Neuroscience, 2024)
Recent literature supports a prominent role for astrocytes in regulation of drug-seeking behaviors. The dorsal striatum, specifically, is known to play a role in reward processing with neuronal activity that can be influenced by astrocyte Ca 2+ . However, the manner in which Ca 2+ in dorsal striatum astrocytes impacts neuronal signaling after exposure to self-administered cocaine remains unclear. We addressed this question following over-expression of the Ca 2+ extrusion pump, hPMCA2w/b, in dorsal striatum astrocytes and the Ca 2+ indicator, GCaMP6f, in dorsal striatum neurons of rats that were trained to selfadminister cocaine. Following extinction of cocaine-seeking behavior, the rats over-expressing hMPCA2w/b showed a significant increase in cue-induced reinstatement of cocaine seeking. Suppression of astrocyte Ca 2+ increased the amplitude of neuronal Ca 2+ transients in brain slices, but only after cocaine self-administration. This was accompanied by decreased duration of neuronal Ca 2+ events in the cocaine group and no changes in Ca 2+ event frequency. Acute administration of cocaine to brain slices decreased amplitude of neuronal Ca 2+ in both the control and cocaine self-administration groups regardless of hPMCA2w/b expression. These results indicated that astrocyte Ca 2+ control over neuronal Ca 2+ transients was enhanced by cocaine self-administration experience, although sensitivity to acutely applied cocaine remained comparable across all groups. To explore this further, we found that neither the hMPCA2w/b expression nor the cocaine self-administration experience altered regulation of neuronal Ca 2+ events by NPS-2143, a Ca 2+ sensing receptor (CaSR) antagonist, suggesting that plasticity of neuronal signaling after hPMCA2w/b over-expression was unlikely to result from elevated extracellular Ca 2+ . We conclude that astrocyte Ca 2+ in the dorsal striatum impacts neurons via cell-intrinsic mechanisms (e.g. gliotransmission, metabolic coupling, etc.) and impacts long-term neuronal plasticity after cocaine self-administration differently from neuronal response to acute cocaine. Overall, astrocyte Ca 2+ influences neuronal output in the dorsal striatum to promote resistance to cue-induced reinstatement of cocaine seeking.